Analysis of Social Values ​​in the Somat Family Cartoon Show Episode “Dudung Is Lost” - Syifa Fauzia (Mitra Palupi, 2022)
Background: Social value is a valuable thing that has to do with the interrelationships and relationships between individuals and other individuals. As social creatures, interaction activities are well adapted and interesting through conventional entertainment media, one of which is cartoon shows. Purpose: The purpose of this study is to find out the social values ​​contained in the